The Presence of Food (In) Security among the Beneficiaries of the Bolsa Família of the Northeast Region of Brazil (Research, Society and Development, 2018)
Several are the factors that corroborate the increase in social inequality in Brazil, among them poverty can be understood as a situation of failure of basic capacities to achieve certain acceptable minimums. In this context, basic needs such as education, health and access to food end up becoming privileged to a society that presents so many inequalities. Thus, the conditional income transfer programmes were designed to break this intergenerational cycle of poverty. This study aims to analyze the presence of the (in) food safety among the beneficiaries of the Family Scholarship program in the northeastern region of Brazil. It is a quantitative and longitudinal study, whose periods analyzed verse between 2004, 2009 and 2013. The main source of data used was the national survey by sample of households. The study concluded that there was an increase in the perception of food safety among the beneficiaries of the family purse in the northeast region for the aforementioned periods.